PARADIGMA BARU PENDIDIKAN MENUJU MASYARAKAT MADANI (TELAAH KRITIS TERKADAP PROBLEM PENDIDIKAN NASIONAL, ARAH KEBIJAKAN, DAN STRATEGI PEMECAHANNYA) - Dadan Rosana Dadan Rosana (Jurnal Cakrawala Pendidikan, 1999)
The educational system and values have developedvery fast, urged by the spirit of reformation in variousaspects of human life. The demand for the formation of acivil society has made education one very effective way toapproach it. For that purpose, there needs to be a changetowards a new paradigm which must be followed with areview on the problems of the national education, thedirection of its policies, and its strategies of problem solving.